2021
DOI: 10.1371/journal.pntd.0009381
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic sequencing reveals viral abundance and diversity in mosquitoes from the Shaanxi-Gansu-Ningxia region, China

Abstract: Background Mosquitoes host and transmit numerous arthropod-borne viruses (arboviruses) that cause disease in both humans and animals. Effective surveillance of virome profiles in mosquitoes is vital to the prevention and control of mosquito-borne diseases in northwestern China, where epidemics occur frequently. Methods Mosquitoes were collected in the Shaanxi-Gansu-Ningxia region (Shaanxi Province, Gansu Province, and Ningxia Hui Autonomous Region) of China from June to August 2019. Morphological methods wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 37 publications
2
38
0
Order By: Relevance
“…Viruses in Aedes , Culex , Anopheles , and Armigeres mosquitoes have been revealed using these methods. Some known viruses have been detected, such as DENV, ZIKV, and West Nile virus [ 39 43 ]. Novel viruses such as the Cuacua virus in Mansonia mosquitoes and the novel orbivirus in Culex fatigans mosquitoes have also been detected [ 37 , 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…Viruses in Aedes , Culex , Anopheles , and Armigeres mosquitoes have been revealed using these methods. Some known viruses have been detected, such as DENV, ZIKV, and West Nile virus [ 39 43 ]. Novel viruses such as the Cuacua virus in Mansonia mosquitoes and the novel orbivirus in Culex fatigans mosquitoes have also been detected [ 37 , 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…Metagenomics studies published in recent years have identified diverse viromes in mosquitoes from around the world [ 31 , 34 , 37 , 43 , 45 , 66 , 90 , 107 , 108 , 109 , 110 , 111 , 112 ].These viromes appear to differ between species and can include anywhere from tens to hundreds of different virus species in a given sample, which often comprises several individuals of a species [ 31 , 34 , 37 , 43 , 45 , 66 , 90 , 107 , 108 , 109 , 110 , 111 , 112 ]. The nearest comparable study to Finland is a single-year, two-location study of 953 specimens of six mosquito species in Sweden [ 90 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the case of viral communities in insects, even recently there was a "biased" conception of viruses as agents that cause disease; however, today, with the advances in metagenomics studies, the proper structural and functional diversity of insect viromes has begun to be elucidated [104][105][106]. Thus, metagenomics methods, especially during the last decade, have provided new insights into the complexity of insect-borne viruses [41,[107][108][109], relevant for active pathogen surveillance and response to emerging and reemerging infectious diseases [37,103,110,111].…”
Section: Metagenomics and The Rise Of Virome Studies In Mosquitoesmentioning
confidence: 99%